The Importance of Religious Tourism and Pilgrimage: reflecting on definitions, motives and data - Griffin, Kevin (The international journal of religious tourism and pilgrimage, 2018)
This discussion paper explores the topic of religious tourism and pilgrimage, examining it from a tourism industry perspective, reflecting on definitions, motivations and scale of the product' as reported at a global level. Mindful of the fact that international records of religious tourism are scant to say the least, this is an attempt to bring together definitions, classifications and data which come from a variety of sources. The paper draws together understandings from different religious traditions, presenting data and motivations on a variety of pilgrimage types. As the paper demonstrates, this niche' product is indeed enormous, and if industry projections are correct, is set to become an even more important element of international travel and tourism.